Effect of different processing methods on the physicochemical properties and sensory evaluations of sweet potatoes chips - Nurul Zaizuliana, Rois Anwar; Asmaliza, Abd. Ghani@Yaacob; Kalaimangai, Sugumaran (2019)
Sweet potatoes is a popular root vegetable and highly nutritious. It is highly perishable and the need of processing required to enable it to be shelf stable. However, some processing methods have been degrading nutrient content of the sweet potatoes while increasing the fat content. Hence, the main aim of this research is to identify sweet potato chips which are nutritious and have acceptable organoleptic properties. Thus, the research also conducted to compare the physicochemical and sensory analysis on two types of sweet potatoes based on different processing methods. The processing methods used were deep-fry, freeze-dry, sun dry, airfry and oven bake methods. The results obtained comparing both types of sweet potatoes mostly did not show statistical significant difference. The physicochemical analysis which shows the nutrition value of sweet potatoes based on different processing methods produced results where the freeze-dried samples tend to have the highest values of ash (1.77 g/100 g), crude protein (5.65 g/100 g) and crude fiber content (3.56 g/100 g). Adversely, freeze-dried samples provided small amount of fat content for both type of sweet potato which are 1.51 g/100 g compared to other samples. However for the sensory acceptance, deep-fried was most acceptable by the panelist with the score of range 5 to 6 in the seven-hedonic scale test. Whereas, the deep-fried sample showed lowest value for the chemical analysis where for ash both type of sweet potatoes (1.19 g/100 g), crude protein (3.74 g/100 g) and crude fiber content (1.62 g/100 g). However, the deep-fried samples had highest fat content for both type of sweet potatoes which are 45.85 g/100 g. Concerning the physical attributes, the sun dried samples had the highest hardness value whereas the freeze-dried samples had the lowest fracturability value which made it least sensory acceptance. Color analysis indicated that orange-fleshed sweet potato (OFSP) retained its colour, but purple-fleshed sweet potato (PFSP) leached its color. Overall, the oven baked samples had moderate amount of ash, crude fiber and crude protein. Besides, it consist lower fat content compared to deep-fried samples. Moreover, oven baked samples obtained similar sensory attributes score of range 5 to 6 as deep-fried samples.